Estimating complete cancer prevalence in Europe: validity of alternative vs standard completeness indexes - Demuru, Elena; Rossi, Silvia; Ventura, Leonardo; Dal Maso, Luigino; Guzzinati, Stefano; Katalinic, Alexander; Lamy, Sebastien; Jooste, Valerie; Di Benedetto, Corrado; De Angelis, Roberta; , the EUROCARE-6 Working Group; Hackl, M.; et al. (Frontiers in Oncology, 2023)
Comparable indicators on complete cancer prevalence are increasingly needed in Europe to support survivorship care planning. Direct measures can be biased by limited registration time and estimates are needed to recover long term survivors. The completeness index method, based on incidence and survival modelling, is the standard most validated approach. Within this framework, we consider two alternative approaches that do not require any direct modelling activity: i) empirical indices derived from long established European registries; ii) pre-calculated indices derived from US-SEER cancer registries. Relying on the EUROCARE-6 study dataset we compare standard vs alternative complete prevalence estimates using data from 62 registries in 27 countries by sex, cancer type and registration time. For tumours mostly diagnosed in the elderly the empirical estimates differ little from standard estimates (on average less than 5% after 10-15 years of registration), especially for low prognosis cancers. For early-onset cancers (bone, brain, cervix uteri, testis, Hodgkin disease, soft tissues) the empirical method may produce substantial underestimations of complete prevalence (up to 20%) even when based on 35-year observations. SEER estimates are comparable to the standard ones for most cancers, including many early-onset tumours, even when derived from short time series (10-15 years). Longer observations are however needed when cancer-specific incidence and prognosis differ remarkably between US and European populations (endometrium, thyroid or stomach). These results may facilitate the dissemination of complete prevalence estimates across Europe and help bridge the current information gaps.